RANCANG BANGUN ALAT PENGEPRESS KULIT NANAS - Nuril Hanan; Syihabuddin Attabrizi; Rodika (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Pineapple fruit is only used for its flesh to be eaten and used for various other forms of food processing. Pineapple skin is thrown away without being used. Traders sell pineapples with the number of pineapples being around 100-120 grains/day. One pineapple produces 0.35 kg of pineapple skin waste, so the pineapple skin waste produced can reach an average of 30-45 kg/day. Pineapple skin waste accumulates and becomes a problem for environmental hygiene. The purpose of this research is to make and build a manual pineapple peel press machine to obtain pineapple peel juice as a raw material for liquid fertilizer. Pineapple skin pulp can be used as animal feed. The stages in the manufacture of this press start from problem identification (field survey, literature study), data collection, design, tool making, assembly, testing, maintenance, conclusion. The capacity of the tool is able to press a maximum of 5 kg of pineapple skin in one process. Experiments were carried out on pineapple skins that were still fresh and which had been stored for 24 hours. Pineapple skin is divided into 2 parts, namely the chopped and non-chopped parts. From pineapple skin that is still fresh and has not been chopped, 1.4 liters of juice are obtained. While the fresh pineapple skin that has been chopped is obtained as much as 1.6 liters of juice. From pineapple skin that has been stored for 24 hours and has not been chopped, 1.5 liters of juice are obtained. While the pineapple skin which was stored for 24 hours and had been chopped obtained 1.7 liters of juice.